Our Vanishing Night - Verlen Klinkenborg (Symphony in the Flint Hills, 2019)
Introduction: If humans were truly at home under the light of the moon and stars, we would go in darkness happily, the midnight world as visible to us as it is to the vast number of nocturnal species on this planet. Instead, we are diurnal creatures, with eyes adapted to living in the sun’s light.